Communications writing and design : the integrated manual for marketing, advertising, and public relations - DiMarco, John, 4 0 16; 5 (Hoboken, NJ : Wiley-Blackwell, 2017)
Communications Writing and Design is an integrated, project-based introduction to effective writing and design across the persuasive domains of communication. -Build a strong foundation of core writing and design skills using professionally-designed examples that illustrate and reinforce key principles -Readers learn and analyze techniques by creating 15 projects in marketing, advertising, PR, and social media with the help of strategy suggestions, practical tips, and professional production techniques -Written by an experienced professional and teacher, with a focus on the cross-disciplinary nature of contemporary communication work -Learning is reinforced through a variety of pedagogical features: learning objectives, helpful mnemonics, real-life projects and applications, chapter references for further study, and end-of-chapter summaries and exercises A companion website with multimedia slides, exam questions, learning videos, and design guides provides additional learning tools for students and instructors.
Online resource; title from PDF title page (EBSCO, viewed March 28, 2017).
Keywords: 2 -- 0; 6; Social aspects. -- Advertising.;Marketing.;Information technology -- 20; 20; Electronic books. -- 2